The Influence of Integrated Marketing Communication of Mom's Willingness to Buy - Sariputra, Yoko; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. The largest portion of monthly food expenditure in Indonesia is packaged food and soft drinks that can be found in modern markets. Through the development of this modern market, the demand for processed packaged foods continues to grow which is able to offer time-saving and convenient ways to eat. One of the food packaging companies that produce the packaged food is Sea-Son Company. This paper will relate one of the business discipline,